Władysław Zdunek. Od „zawodowego rewolucjonisty” do „elementu reakcyjnego”. Biografia działacza - Drabik, Rafał (Komunizm: System - Ludzie - Dokumentacja, 2015)
The life of Wladyslaw Zdunek was full of radical changes. He fought with the communists in the Polish-Soviet War in 1920. A few years later he became a union activist in the Communist Party. During the whole period until the outbreak of second world war in various ways to support institutions that sympathized with the Communists. He was stopped many times by the Polish police, also he sat for it in prison. Although became an important person in the communist party in the Lublin province it is his character traits didn't let him the political career. He was quickly sidelined track. It caused more reasons for dissatisfaction.For the communist police became the enemy, which under surveillance and observed. His life is an example of that in the communist period did not really mattered education, but acquaintances in the elite party nomenclature. Although his life you can find many examples of typical careerism, however, character traits and attitudes instability did not allow him on achieving any successes